KNOWLEDGE OF GOVERNMENT AND PRIVATE PRIMARY HEALTH CARE WORKERS ON NEWBORN CARE COMPONENTS: A QUESTIONNAIRE-BASED CROSS-SECTIONAL COMPARATIVE STUDY - J, Pandiamunian; T, Ishwarya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: This study was done to evaluate the knowledge of primary health-care workers about the newborn care components. Methods: The Institutional Ethics Committee approval was obtained, and a cross-sectional study was carried out among the primary health-care workers of Karaikal using a pretested questionnaire from January 2015 to March 2015. The questionnaire contained questions on various domains of newborn care components. The study participants were explained about the study. Verbal informed consent was obtained, and the questionnaire was introduced to 383 health-care workers. The answered questionnaires were collected and analyzed. Results: A total of 349 participants (192-government employees; 157-private employees) were willing to take part in the study. Most (54.7%) of the government participants were nurses and auxiliary nurse midwives (43.2%) whereas the private sector participants were predominantly (79%) nurses. The knowledge level about some of the newborn care components, namely, positioning and attachment, advice on discharge, time of follow-up checkup, bad child rearing practices, and danger signs of newborn were assessed to be predominantly inadequate among a majority of health workers of both sectors. 22.29% and 41.1% of the private health-care workers and government health-care workers respectively, were having an overall adequate knowledge (overall score >75%) on newborn care components. Knowledge of the government health workers was significantly better than private health-care staff (P < 0.001). Conclusion: Knowledge is found to be inadequate among health-care workers on some newborn care components which necessitate measures to improve. Keywords: Newborn care, Nurses, Midwives, Inadequate knowledge, Training programs. Â 